Congenital Cytomegalovirus Infection: Update on Diagnosis and Treatment - Giulia Chiopris; Piero Veronese; Francesca Cusenza; Michela Procaccianti; Serafina Perrone; Valeria Daccò; Carla Colombo; Susanna Esposito (Microorganisms, 2020)
Congenital cytomegalovirus (cCMV) infection is the most common congenital viral infection and is the leading non-genetic cause of sensorineural hearing loss (SNLH) and an important cause of neurodevelopmental disabilities. The risk of intrauterine transmission is highest when primary infection occurs during pregnancy, with a higher rate of vertical transmission in mothers with older gestational age at infection, while the risk of adverse fetal effects significantly increases if fetal infection occurs during the first half of pregnancy. Despite its prevalence and morbidity among the neonatal population, there is not yet a standardized diagnostic test and therapeutic approach for cCMV infection. This narrative review aims to explore the latest developments in the diagnosis and treatment of cCMV infection. Literature analysis shows that preventive interventions other than behavioral measures during pregnancy are still lacking, although many clinical trials are currently ongoing to formulate a vaccination for women before pregnancy. Currently, we recommend using a PCR assay in blood, urine, and saliva in neonates with suspected cCMV infection. At present, there is no evidence of the benefit of antiviral therapy in asymptomatic infants. In the case of symptomatic cCMV, we actually recommend treatment with oral valganciclovir for a duration of 12 months. The effectiveness and tolerability of this therapy option have proven effective for hearing and neurodevelopmental long-term outcomes. Valganciclovir is reserved for congenitally-infected neonates with the symptomatic disease at birth, such as microcephaly, intracranial calcifications, abnormal cerebrospinal fluid index, chorioretinitis, or sensorineural hearing loss. Treatment with antiviral drugs is not routinely recommended for neonates with the mildly symptomatic disease at birth, for neonates under 32 weeks of gestational age, or for infants more than 30 days old because of insufficient evidence from studies. However, since these populations represent the vast majority of neonates and infants with cCMV infection and they are at risk of developing late-onset sequelae, a biomarker able to predict long-term sequelae should also be found to justify starting treatment and reducing the burden of CMV-related complications.